1992
DOI: 10.1159/000261492
|View full text |Cite
|
Sign up to set email alerts
|

Limitations in the Intraoral Demineralization of Bovine Enamel

Abstract: A model system was used to examine the relation between the duration of plaque pH fall and enamel demineralization following the intake of dietary carbohydrate in humans. Subjects wore palatal appliances containing blocks of bovine enamel covered with Streptococcus mutans IB 1600, and rinsed with 5 or 10% sucrose. Changes in iodide penetrability (delta Ip) of the enamel, and the pH and extracellular calcium and inorganic phosphate (Pi) concentrations of the streptococcal plaque were determined. Following rinse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
2
6
0
1
Order By: Relevance
“…Interestingly, the results with the sweet cookies showed that demineralization reac hed a maximum, so that the entrapped cookie particles did not sustain a continued, progressive demineralization. This apparent limit to the degree of demineralization was similar to that encountered with repeated rinses of sucrose [Kashket and Yaskell, 1992], Evidently, the initial concentrations of plaque sugar are most important in determining the subse quent course and degree o f enamel demineralization.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, the results with the sweet cookies showed that demineralization reac hed a maximum, so that the entrapped cookie particles did not sustain a continued, progressive demineralization. This apparent limit to the degree of demineralization was similar to that encountered with repeated rinses of sucrose [Kashket and Yaskell, 1992], Evidently, the initial concentrations of plaque sugar are most important in determining the subse quent course and degree o f enamel demineralization.…”
Section: Discussionsupporting
confidence: 58%
“…Raw calculations of the ion activity products of the fluids suggest that saturation with respect to hydroxyapatite and fluorapatite is being reached (considering 40% of total Ca in the fluid free [Vogel et al, 1998[Vogel et al, , 2000a and ionic strength is 150 m M [Margolis et al, 1988], pKIAP HAp ; 119, pKIAP FAp ; 112, Chemist version 1.0.1, Salt Lake City, Utah, USA). This indicates that the increase in Ca concentration in the fluid would be a self-limiting step for dental demineralization soon after exposure of the biofilm to carbohydrates, as discussed previously [Kashket and Yaskell, 1992].…”
Section: Resultssupporting
confidence: 60%
“…Using 10% sucrose+F at 10 ppm, we have noted no differences in plaque pH changes compared with using sucrose alone. Lack of F effect of these levels on the plaque pH response to sucrose supports the findings of Kashket and Yaskell (1992). Using intra-oral appliances and 10% sucrose rinses, Pearce et al (1992) reported pH drops to 4.0 and 4.8, but these changes did not correlate with enamel demineralization.…”
Section: Effect Of F Concentration On Plaque Phmentioning
confidence: 73%